46,XX Testicular Disorders of Sex Development With DMD Gene Mutation: First Case Report Identified Prenatally by Integrated Analyses in China - Deng, Jianlian; Zhang, Haoqing; Li, Caiyun; Huang, Hui; Liu, Saijun; Yang, Huanming; Xie, Kaili; Wang, Qiong; Lei, Dongzhu; Wu, Jing (Frontiers in Genetics, 2020)
The present study describes the first prenatally diagnosed 46,XX testicular disorders of sex development(46,XX testicular DSD) case with DMD gene mutation by integrated analyses in a Chinese pedigree. Chromosome karyotype G-banding analysis of the proband showed a 46,XX karyotype, but B-ultrasound analysis demonstrated the existence of scrotum, testis and penis which inferred a male sexual differentiation. Aneuploidy and Copy number variation (CNV) detection by low-coverage single-end whole genome sequencing (WGS) revealed a de novo SRY (Sex-determining region Y) gene positive fragment of 224.34 Kb length (chrY:2,649,472-2,873,810) which explained the gonadal/genital-chromosomal inconsistency in the proband. Additionally, targeted-region-capture-based DMD gene sequencing and Sanger verification confirmed a widely reported pathogenic heterozygous nonsense mutation (NM_004006, c.9100C>T, p.Arg3034Ter) in the dystrophin-coding gene named DMD. This study emphasizes that integrated analyses of the imaging results, cytogenetics, and molecular features can play an important role in prenatal diagnosis. It requires the combination of more detection techniques with higher resolution than karyotyping to determine the genetic and biological sex of fetuses in prenatal diagnosis. To conclusively determine both the biological and genetic sex of the fetus at the time of prenatal diagnosis particularly in cases that involve X-linked conditions is of vital importance, which would crucially influence the decision-making regarding abortions. This study will help in prenatal diagnosis of DMD in future, also providing a new perspective that enables the genetic diagnosis of sex reversal in pregnancy. Moreover, genetic counseling/analysis for early diagnosis and pre-symptom interventions are warranted.